HUMAN AND ROBOT COLLABORATION ASSEMBLY LINE MODEL DEVELOPMENT TAKING INTO THE SETUP TIME - Mahardini, Ladzwina
Technological developments allow robots to work side by side with humans because robots are equipped with work safety sensors to prevent collisions with humans. The use of human-robot collaboration can also be applied across assembly lines. Research on the assembly line of human and robot collaboration has been carried out, but the current research has not considered setup time. Setup time needs to be considered because in actual conditions there is setup time, so it is necessary to develop a cross-assembly model for human and robot collaboration by considering setup time. The developed mathematical model aims to minimize cross-assembly costs to produce one type of product by considering several resource options taking into account the setup time. There are three resources considered, namely humans, robots, and human-robot collaboration. The results of the model test show that the setup time can affect the optimal solution. If the initial availability of robotic resources is not yet available, then there is a tendency to choose humans as assembly resources. In this case, the setup time also does not significantly affect the optimal solution. Meanwhile, if the initial robot resources are already available, then the setup time needs to be considered because it affects the optimal solution.